Lesbian, Gay , Bisexual dan Transgender Penyembuhan dan Upaya Membentuk Kepribadian Islami di Era Generasi Millenial melalui Psikoterapi Islam - B, Ahmad Andry (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2018)
This article basically discusses how to form a millennial generation of Islamic personality whose main focus is to cure adolescents infected with lesbian, gay, bisexual and transgender (LGBT) viruses.the rapid development of technology and the ease of accessing the internet have become the entrances to the millennial LGBT virus, so as to cure teenagers infected by LGBT virus, one of the is Islamic psychotherapy which uses sufism or tasawwuf approaches including takhalli, tahalli and tajalli. Islamic psychotherapy can cure several diseases, namely mental, spiritual and moral disorders, even delivering humans to Islamic personalities who are pious, clean, holy and find the existence of an essential god.